1992
DOI: 10.1017/s174275840001359x
|View full text |Cite
|
Sign up to set email alerts
|

Cowpea plant architecture in relation to infestation and damage by the legume pod borer, Maruca testulalis Geyer (Lepidoptera: Pyralidae) — 2. Effect of pod angle

Abstract: The effect of pod angle on the resistance of cowpea, Vigna unguiculata (L.) Walp. to the legume pod borer, Maruca testulalis Geyer, was investigated under field conditions at the International Institute of Tropical Agriculture (IITA), Ibadan, Nigeria, using two cowpea cultivars: IT82D-716 (susceptible to borer damage) and T Vu 946 (resistant to borer damage). Three different pod angles were used in the study -a normal angle, a decreased angle and an increased angle. Negative and highly significant (P < 0.01) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…Cowpea genotypes with bunched pods suffer greater damage (Usua and Singh, 1979). Oghiakhe et al (1992b) observed negative relationships between pod angle and pod damage, and seed damage index in two cowpea cultivars. Pods with wide angles ( > 89") were damaged on one side, and rarely on both sides.…”
Section: Factors Associated With Resistancementioning
confidence: 82%
“…Cowpea genotypes with bunched pods suffer greater damage (Usua and Singh, 1979). Oghiakhe et al (1992b) observed negative relationships between pod angle and pod damage, and seed damage index in two cowpea cultivars. Pods with wide angles ( > 89") were damaged on one side, and rarely on both sides.…”
Section: Factors Associated With Resistancementioning
confidence: 82%
“…The past few decades have also seen the identification of a staggering number of secondary plant chemicals that function in resistance to herbivory (Fraenkel, 1959; Norris & Kogan, 1980; Hartmann, 1996; Harborne, 1997; Pichersky & Gang, 2000). More recently, researchers have begun to appreciate that aspects of a plant's growth form may also influence the likelihood of herbivore attack (Oghiakhe et al ., 1992; Alonso & Herrera, 1996; Araújo et al ., 2006; Chang et al ., 2006; Rudgers & Whitney, 2006). Although architectural traits have obvious importance for plant growth, some may turn out to function mainly as adaptations to resist herbivory (Marquis et al ., 2002; Grubb & Jackson, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…While chemical toxins and mechanical deterrents dominate the arsenal of known or suspected herbivore defenses in plants, architectural features of plants may also serve important roles in plant resistance (Lawton 1983, Kareiva and Sahakian 1990, Alonso and Herrera 1996, Espı´rito-Santo et al 2007. Investigators have identified a variety of architectural characteristics that can affect resistance to herbivory, including number of buds, branches, or flowers (Oghiakhe et al 1993, Arau´jo et al 2006), size of internodes (Larson and Whitham 1997), spacing of leaves (Marquis et al 2002), rolling of young leaves (Grubb and Jackson 2007), pod angle (Oghiakhe et al 1992), growth habit (e.g., erect, prostrate, or spreading [Oghiakhe et al 1993, Rudgers andWhitney 2006]), and architectural complexity in general (Kaitaniemi et al 2004). Perhaps the most basic feature of plant architecture, however, is size.…”
Section: Introductionmentioning
confidence: 99%